Human governance: a neglected mantra for continuous performance improvement - Salleh, Arfah; Ahmad, Aziuddin; Samy, Naresh Kumar (International Society for Performance Improvement, 2009)
Every individual should be entrusted with an internal driver to strive their best towards achieving their potential and to manifest their performance through innovative means. This can be reached only under circumstances where the abstract human values and principles are recognized and indoctrinated in the culture. The strategies discussed in this article will serve as input in proposing the areas of focus toward the practice of human governance.